Abnormal methylation in the NDUFA13 gene promoter of breast cancer cells breaks the cooperative DNA recognition by transcription factors. (28th November 2022) - Hörberg, Johanna; Hallbäck, Björn; Moreau, Kevin; Reymer, Anna
Abstract: Abstract: Selective DNA binding by transcription factors (TFs) is crucial for the correct regulation of DNA transcription. In healthy cells, promoters of active genes are hypomethylated. A single CpG methylation within a TF response element (RE) may change the binding preferences of the protein, thus causing the dysregulation of transcription programs. Here, we investigate a molecular mechanism driving the downregulation of the NDUFA13 gene, due to hypermethylation, which is associated with multiple cancers. Using bioinformatic analyses of breast cancer cell line MCF7, we identify a hypermethylated region containing the binding sites of two TFs dimers, CEBPB and E2F1-DP1, located 130 b.p. from the gene transcription start site. All-atom extended MD simulations of wild type and methylated DNA alone and in complex with either one or both TFs dimers provide mechanistic insights into the cooperative asymmetric binding order of the two dimers; the CEBPB binding should occur first to facilitate the E2F1-DP1–DNA association. The CpG methylation within the E2F1-DP1 RE and the linker decrease the cooperativity effects and renders the E2F1-DP1 binding site less recognizable by the TF dimer. Taken together, the identified CpG methylation site may contribute to the downregulation of the NDUFA13 gene.